The extended family and intrahousehold allocation: inheritance and investments in children in the rural Philippines - Quisumbing, Agnes R. (International Food Policy Research Institute, 1995)
This paper examines the role of the extended family on investments in children, using data from a retrospective survey of three generations in the rural Philippines. Econometric results show that interactions between grandparent characteristics and child gender significantly affect the distribution of proposed land bequests between sons and daughters. However, grandparents significantly affect gender-specific investments in children's education only in resource-constrained families. Family-specific effects are more important in determining the pattern of investment in children within the nuclear family, while individual heterogeneity rather than family-specific unobservables dominates the extended family results. Interactions between parent characteristics and child gender are important determinants of both land transfers to, and educational investments in, children. Sons are clearly favored in terms of land inheritance, although daughters of better educated fathers, and with better educated grandfathers, may also have an advantage. The secular expansion of education has contributed much to the increased educational attainment of women. Better educated fathers favor daughters in terms of education, while mothers with more land favor sons. These patterns are consistent with both equity and efficiency objectives, investment in children under resource constraints, and parents' risk-diversification strategies.